2022
DOI: 10.18632/aging.204375
|View full text |Cite
|
Sign up to set email alerts
|

Krill oil protects dopaminergic neurons from age-related degeneration through temporal transcriptome rewiring and suppression of several hallmarks of aging

Abstract: There is accumulating evidence that interfering with the basic aging mechanisms can enhance healthy longevity. The interventional/therapeutic strategies targeting multiple aging hallmarks could be more effective than targeting one hallmark. While health-promoting qualities of marine oils have been extensively studied, the underlying molecular mechanisms are not fully understood. Lipid extracts from Antarctic krill are rich in longchain omega-3 fatty acids choline, and astaxanthin. Here, we used C. elegans and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…We computed age-correlations of z-score normalized gene counts for all human brain regions in the GTEx dataset 33 , the Tabula Muris Senis (TMS) dataset 5 , and an additional mouse Hypothalamus aging cohort (GSE157025). Similarly, we calculated the enriched pathways for several "anti-aging" treatments like young serum injections 34 , the platelet factor PF4 35 , sport in humans 36 , and krilloil in C. elegans 37 . An unbiased clustering analysis revealed that the aging-trajectories of C. elegans, mouse, and humans cluster together.…”
Section: Comparison With Mammalian Brain Agingmentioning
confidence: 99%
“…We computed age-correlations of z-score normalized gene counts for all human brain regions in the GTEx dataset 33 , the Tabula Muris Senis (TMS) dataset 5 , and an additional mouse Hypothalamus aging cohort (GSE157025). Similarly, we calculated the enriched pathways for several "anti-aging" treatments like young serum injections 34 , the platelet factor PF4 35 , sport in humans 36 , and krilloil in C. elegans 37 . An unbiased clustering analysis revealed that the aging-trajectories of C. elegans, mouse, and humans cluster together.…”
Section: Comparison With Mammalian Brain Agingmentioning
confidence: 99%
“…Neurodegeneration, protein aggregation, mitochondrial dysfunction, and reactive oxygen species formation are endpoints well explored in both PD and AD C. elegans models (Naranjo-Galindo et al 2022 ; SenGupta et al 2021 ). Worth mentioning, that steadily piling omics approaches in C. elegans AD and PD model allow for investigation of the molecular mechanism underlying DNT and ANT (SenGupta et al 2022 ; Sánchez-Martínez et al 2023 ).…”
Section: Nams and Neurotoxicity Assessmentmentioning
confidence: 99%